Cladocera (Crustacea: Branchiopoda) of Sabah state in Borneo Island, Malaysia - Sinev, Artem Y.; Md. Yusoff, Fatimah (Magnolia Press, 2015)
Fauna of Cladocera (Crustacea: Branchiopoda) of Sabah state of Malaysia, Borneo Island, was evaluated for the first time. Samples from 40 locations were studied, and 31 species of Cladocera were revealed, including three species of Sididae, one species of Daphnidae, one species of Moinidae, four species of Macrothricidae, two species of Ilyocryptidae, and 20 species of Chydoridae. One species of Ilyocryptidae, Ilyocryptus yooni Jeong, Kotov and Lee, 2012, is recorded for Malaysia for the first time, and one more, Anthalona sp., is probably new for science. Of 31 species recorded for Sabah, only three are true planktonic species and 28 are substrate-associated species. Absence of large natural lakes, habitats with most rich cladoceran fauna, can be an important factor limiting diversity of Cladocera in Sabah